HPLC-Based Activity Profiling for Antiprotozoal Compounds in Croton gratissimus and Cuscuta hyalina - Mahmoud, Abdelhalim Babiker; Danton, Ombeline; Kaiser, Marcel; Khalid, Sami; Hamburger, Matthias; Mäser, Pascal (Frontiers in Pharmacology, 2020)
In a screening of Sudanese medicinal plants for antiprotozoal activity, the chloroform fractions obtained by liquid-liquid partitioning from ethanolic extracts of fruits of Croton gratissimus var. gratissimus and stems of Cuscuta hyalina Roth ex Schult. exhibited in vitro activity against axenically grown Leishmania donovani amastigotes. This antileishmanial activity was localized by HPLC-based activity profiling. Targeted preparative isolation afforded flavonoids 1-6, 3-methoxy-4-hydroxybenzoic acid (7), and benzyltetrahydroisoquinoline alkaloids laudanine (8) and laudanosine (9) from C. gratissimus, and pinoresinol (10), isorhamnetin (11), (-)-pseudosemiglabrin (12), and kaempferol (13) from C. hyalina. The antiprotozoal activity of 1-13 against Leishmania donovani (axenic and intracellular amastigotes), Trypanosoma brucei rhodesiense (bloodstream forms), and Plasmodium falciparum (erythrocytic stages), and the cytotoxicity in L6 murine myoblast cells were determined in vitro. Quercetin-3,7-dimethylether (6) showed the highest activity against axenic L. donovani (IC50 4.5 µM, selectivity index (SI) 12.3), P. falciparum (IC50 7.3 µM, SI 7.6) and T. b. rhodesiense (IC50 2.4 µM, SI 23.2). The congener ayanin (2) exhibited moderate antileishmanial (IC50 8.2 µM, SI 12.2), antiplasmodial (IC50 7.8 µM, SI 12.9) and antitrypanosomal activity (IC50 11.2 µM, SI 8.9). None of the compounds showed notable activity against the intramacrophage form of L. donovani.